Changes in cell morphology guide identification of tubulin as the off-target for protein kinase inhibitors. (August 2018) - Hoque, Monira; Abbassi, Ramzi H.; Froio, Danielle; Man, Jennifer; Johns, Terrance G.; Stringer, Brett W.; Day, Bryan W.; Pajic, Marina; Kassiou, Michael; Munoz, Lenka
Graphical abstract: Abstract: In the field of kinase inhibitors for applications in cancer research, tubulin is emerging as a targeted cellular protein that can significantly contribute to their activities. However, investigation of kinase inhibitors beyond the kinome is an area often neglected. Herein, we describe the results of pharmacological studies using drugs targeting kinases, tubulin or both. A key finding is that if cells are treated with a kinase inhibitor unintentionally targeting tubulin, their characteristic shape will diminish within a short timeframe. These changes in cell morphology are not seen when cells are treated with bona fide kinase inhibitors that do not directly target tubulin. Thus, early changes in cell morphology upon treatments are a strong indication that the inhibitor is directly targeting tubulin. Recognizing tubulin as a target of kinase inhibitors will build confidence in the future mechanistic studies using kinase inhibitors.